Anti-Human Leukocyte Antigen Antibody Induced Autoimmunity: Role In Chronic Rejection - Nath, DS (2010)
PURPOSE OF REVIEW: We provide evidence for the role of de novo development of immune responses to self-antigens in the post-transplant period and its possible induction by alloimmunity in the pathogenesis of chronic rejection following lung, heart and kidney transplantation. This review details recent findings for the two distinct yet inter-dependent immune processes in the immune-pathogenesis of chronic rejection. RECENT FINDINGS: The contribution of both humoral and cell mediated allo-immune responses against mismatched donor histocompatibility antigens (HLA) in the pathogenesis of chronic rejection is well established. Recent studies have focused on development of immune responses to self-antigens during the post-transplant period and its correlation with chronic rejection. These self-antigens include myosin and vimentin in cardiac, K-alpha-1-tubulin and collagen-V in lung and angiotensin II type 1 receptor, collagen-IV and VI in kidney transplants. During the post-transplant period, the development of immune responses to self-antigens is facilitated by induction of a distinct subset of auto-reactive T-helper cells referred to as Th17 cells. SUMMARY: Following organ transplantation, tissue injury and remodeling inflicted by Abs to HLA antigens is conducive to develop autoimmunity. Antibodies (Abs) to HLA and self-antigens are detectable in the serum of transplant recipients who develop chronic rejection. Anti-HLA Abs are often present transiently but precede the development of Abs to self-antigens.